Pit and Fissure Sealants in Caries Prevention: Materials, Techniques, and Evidence-Based Outcomes (Academia Journal of Medicine, 2026)
Dental caries is among the most common chronic diseases in the world that is disproportionately present in the occlusal surfaces of the posterior teeth with complex morphology of pits and fissures where there is the presence of biofilm and conducive demineralization by acid. Pit and fissure sealants are one of the prevention measures that serve as a strategy due to their ability to cause a barrier between the exposed tooth surface and the oral environment, and hence the prevention of bacterial colonization and consequent carious lesions. This narrative review focuses on the current evidence on the topic of pit and fissure sealants, including the history of sealant materials, the mechanisms of their application, their retention, their caries-preventive effectiveness, and their cost-effectiveness. The review combines the results of clinical trials, systematic reviews, meta-analyses that were carried out during a number of decades to present an all-encompassing evaluation of the purpose of sealants in modern preventive dentistry. Some of the key themes covered are comparative efficacy of resin based and glass ionomer sealants, effects of isolation and surface preparation methods on the retention of sealants, the use of sealants over incipient carious lesions and new bioactive materials. The literature is consistently in favor of the efficacy of pit and fissure sealants in preventing the occlusal caries by 60 to 90 percent when properly retained, and best results are noticed in the high risk groups. Nevertheless, there are some gaps in terms of long term follow up data, the best choice of material to use in different clinical settings, and what should be done to enhance sealant programs in underserved communities. The review shows that the application of sealants must be incorporated into an overall plan of managing caries and also provides an insight into the future opportunities in material science and policy development.
Keywords: pit and fissure sealants, dental caries prevention, resin-based sealants, glass ionomer cement, caries risk assessment, evidence based dentistry, preventive dentistry